Diction in Trilogy Novel Negeri 5 Menara by Ahmad Fuadi Stylistic Studie (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Dictionary is the choice of words used by authors in literary works. In connection with the diction, the trilogy novel Negeri 5 Menara by Ahmad Fuadi tried to attract readers one of them through diction. The study of stylists in it is diction, because diction is part of the language style. The purpose of this study is to describe the choice of words contained in the novel. The method used in this research is semiotic-structuralism method with hermeneutic technique, using stilistika approach. The results of the study show that there are six diction uses of which the choice of foreign words (Arabic, English and French) with the number of 200 words, the word from the local language (Minang Language, Javanese, Sundanese and Betawi Language) amounted to 141 words, a typical greeting from the local language (Minang typical greeting, Javanese greeting) with 13 words. Then the use of the word exclamation amounted to 12 words, 51 words of connotative words, and words with objects of natural reality amounted to 11 words. The result of research shows that foreign language word is the most dominant word choice used by author, while word with object of natural reality is word choice which is not dominant.